Biocontrol ability and action mechanism of Metschnikowia citriensis against Geotrichum citri-aurantii causing sour rot of postharvest citrus fruit. (May 2020) - Wang, Shupei; Ruan, Changqing; Yi, Lanhua; Deng, Lili; Yao, Shixiang; Zeng, Kaifang
Abstract: This study investigated the biocontrol efficiency of Metschnikowia citriensis strain FL01 against Geotrichum citri-aurantii, and evaluated possible mechanisms. The results showed that M. citriensis could effectively control the development of sour rot, and significantly inhibit the mycelial growth and spore germination of G. citri-aurantii . The population dynamics results and Scanning electron microscopy (SEM) analysis indicated that M. citriensis could rapidly colonize wounds and tightly adhere to the surface of the wounds to compete with G. citri-aurantii for nutrition and space. M. citriensis also showed the biofilm formation action in vitro. The response of G. citri-aurantii to different components of M. citriensis culture showed that only the yeast cells but not the extracellular metabolites and the volatile organic compounds (VOCs) exhibited inhibitory effect on the growth of G. citri-aurantii . M. citriensis adhered to the hyphae of G. citri-aurantii loosely and sparsely, and the production of lytic enzymes β-1, 3-glucanase (GLU) and Chitinase (CHI) could not be induced by G. citri-auranti . Iron affected the pulcherrimin pigment production and antagonism of M. citriensis indicating iron depletion as the most important antagonistic mechanism. Besides, M. citriensis also induced resistance of fruit against sour rot. These results suggested that M. citriensis could be used as the potential alternative of fungicides to control postharvest pathogens on citrus fruit. Highlights: M. citriensis could effectively control the sour rot caused by G. citri-aurantii. M. citriensis have the capacity of wound colonization and biofilm formation. M. citriensis could deplete iron inhibited the growth of G. citri-aurantii.